Analisis Pesan Moral Film Pendek PT Kereta Api Indonesia “Ruang Tunggu” Karya Galih Firdaus: (Analisis Semiotika Charles Sanders Pierce) - Aditya Alif Saputro; Harmonis Harmonis (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2026)
Film is a communication medium capable of conveying moral messages to the public through a series of moving images, usually accompanied by sound. One such medium is the short film. "The waiting room" by Galih Firdaus, a production of PT Kereta Api Indonesia (KAI) released in April 2024 and received positive acclaim for its engaging plot and relevance to the audience's reality. This study aims to analyze the moral message in the film using Charles Sanders Pierce's semiotic theory, which emphasizes three main elements: Representation, Object, and Interpretant. The study used a descriptive qualitative approach with a content analysis method to uncover the moral meanings behind the film's scenes. The results found 15 scenes that explicitly convey moral values, including the importance of open communication within the family, the meaning of simple kindness, valuing togetherness, the commitment of true love, a mother's fortitude, loyalty in waiting, and sincere care. The moral message is constructed through Representation (physical signs such as a bowl of soto), Object (the reality conveyed, such as an apology), and Interpretant (the audience's understanding that the soto symbolizes improving relationships). In conclusion, the film "The waiting room" successfully conveys a strong moral message through a neatly structured narrative.